2018
DOI: 10.1002/hipo.22832
|View full text |Cite
|
Sign up to set email alerts
|

CA1 pyramidal neuron gene expression mosaics in the Ts65Dn murine model of Down syndrome and Alzheimer's disease following maternal choline supplementation

Abstract: Although there are changes in gene expression and alterations in neuronal density and afferent inputs in the forebrain of trisomic mouse models of Down syndrome (DS) and Alzheimer's disease (AD), there is a lack of systematic assessments of gene expression and encoded proteins within individual vulnerable cell populations, precluding translational investigations at the molecular and cellular level. Further, no effective treatment exists to combat intellectual disability and basal forebrain cholinergic neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 151 publications
4
51
0
Order By: Relevance
“…Recently, studies have demonstrated that dietary MCS during pregnancy and lactation attenuates cognitive dysfunction and BFCN degeneration in adult Ts65Dn progeny (Moon et al , ; Ash et al , ; Kelley et al , ; ; Strupp et al , ; Powers et al , ). Despite the importance of the cholinergic basal forebrain projection system in cognitive function, little is known about the molecular pathobiology of BFCNs in DS (Chrast et al , ; Alldred et al , ; ; ; Perez et al , ). Here, we present single population neuronal expression data showing alterations to the transcriptional signature of MS/VDB cholinergic neurons obtained from offspring of Ts65Dn dams treated with MCS or a choline‐controlled diet during gestation and nursing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have demonstrated that dietary MCS during pregnancy and lactation attenuates cognitive dysfunction and BFCN degeneration in adult Ts65Dn progeny (Moon et al , ; Ash et al , ; Kelley et al , ; ; Strupp et al , ; Powers et al , ). Despite the importance of the cholinergic basal forebrain projection system in cognitive function, little is known about the molecular pathobiology of BFCNs in DS (Chrast et al , ; Alldred et al , ; ; ; Perez et al , ). Here, we present single population neuronal expression data showing alterations to the transcriptional signature of MS/VDB cholinergic neurons obtained from offspring of Ts65Dn dams treated with MCS or a choline‐controlled diet during gestation and nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrocellulose membranes with embedded probes were used for hybridization of cDNA, as described previously (Alldred et al , ). Membranes were stripped in a weak base (0.4N NaOH) in glass tubes placed in a rotating hybridization oven (45 min at 45°C), rinsed (0.2 M Tris pH 7.2, 0.1% SDS 10% (Gibco), 0.1% SSC 20X (Fisher); 1X 1 min, 2X 10 min, 20°C), and incubated in a prehybridization buffer (formamide, Denhardts solution, 20X SSPE (Ambion), 0.1% SDS, and boiled sheared salmon sperm DNA (Ambion) in DEPC‐treated H 2 O; 4 h, 42°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these studies examined admixed neuronal, glial, and vascular cell populations and, in some cases, multiple admixed brain regions. Previous work in our lab has shown that MCS attenuated or reversed a subset of transcripts whose aberrant gene expression was seen in the murine DS phenotype (Ts65Dn mice) compared with 2N controls (51). Because of the large and complex datasets emanating from these single population analyses, global MCS gene expression level changes within CA1 pyramidal neurons stratified by age or genotype have not been performed, which are crucial to understand what MCS does mechanistically to gene expression within a vulnerable hippocampal cell type in an aging paradigm relevant toward understanding the pathophysiology of DS and AD.…”
mentioning
confidence: 81%
“…A second independent, mixed-gender cohort of ;6-mo-old mice (n = 9/condition for 2N + , 2N, Ts + , and Ts) was perfused with 0.1 M phosphate buffer, and the CA1 subregion was microdissected tissue as previously described (51,62,63) and RNA extracted for quantitative PCR (qPCR) and NanoString nCounter (NanoString Technologies; Seattle, WA, USA) analyses. Taqman qPCR primers (Thermo Fisher Scientific) were utilized for the following genes: CREB binding protein (Crebbp; Mm01342452_m1), embryonic lethal abnormal vision-like 1 (Elavl1; m01243908_m1), and G-protein, a-z polypeptide (Gnaz; Mm01150269_m1).…”
Section: Quantitative Pcr and Nanostring Ncountermentioning
confidence: 99%